Analysis of the dimensional stability of alginate during six days after its manipulation (Research, Society and Development, 2022)
Introduction: Alginate is one of the most used elements in dental practice, its reproduction is commonly generated in the first consultation, being essential to build a primitive idea about the patient's level of oral well-being. Purpose: to explain the storage time and storage method of alginate after handling so that dimensional stability is guaranteed, through a cross-sectional field survey. Methodology: This is a laboratory test to be carried out at the multidisciplinary Laboratory of the Fametro University Center, with a qualitative approach. Results: When an analysis is carried out by material, it is observed that the CAVEX brand alginate has the highest average weight and length and the HYDROGUM 5 brand has the lowest average weight, but with an average length similar to that of the CAVEX brand. Conclusion: it was shown that the impressions of the tested alginates must be poured immediately after removal from the patient's mouth so that the impression is accurate and stable.